THE MEMORIA APOSTOLORUM ON THE VIA APPIA - Jones, H. Stuart (The journal of theological studies, 1926)
H. STUART JONES; THE MEMORIA APOSTOLORUM ON THE VIA APPIA, The Journal of Theological Studies, Volume os-XXVIII, Issue October, 1 October 1926, Pages 30–39, htt